Pseudomonas aeruginosa PAO 1 In Vitro Time-Kill Kinetics Using Single Phages and Phage Formulations-Modulating Death, Adaptation, and Resistance - Ana Mafalda Pinto; Alberta Faustino; Lorenzo M. Pastrana; Manuel Bañobre-López; Sanna Sillankorva (MDPI AG, 2021)
Pseudomonas aeruginosa is responsible for nosocomial and chronic infections in healthcare settings. The major challenge in treating P. aeruginosa-related diseases is its remarkable capacity for antibiotic resistance development. Bacteriophage (phage) therapy is regarded as a possible alternative that has, for years, attracted attention for fighting multidrug-resistant infections. In this work, we characterized five phages showing different lytic spectrums towards clinical isolates. Two of these phages were isolated from the Russian Microgen Sextaphage formulation and belong to the Phikmvviruses, while three Pbunaviruses were isolated from sewage. Different phage formulations for the treatment of P. aeruginosa PAO1 resulted in diversified time-kill outcomes. The best result was obtained with a formulation with all phages, prompting a lower frequency of resistant variants and considerable alterations in cell motility, resulting in a loss of 73.7% in swimming motility and a 79% change in swarming motility. These alterations diminished the virulence of the phage-resisting phenotypes but promoted their growth since most became insensitive to a single or even all phages. However, not all combinations drove to enhanced cell killings due to the competition and loss of receptors. This study highlights that more caution is needed when developing cocktail formulations to maximize phage therapy efficacy. Selecting phages for formulations should consider the emergence of phage-resistant bacteria and whether the formulations are intended for short-term or extended antibacterial application.